The Effect of Size of Deep Learning Models in Science Learning - Santosa, Tomi Apra (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The study found out the influence of the deep learning model in science learning. This research is a type of quantitative research with a meta-analysis approach. The source of research data is 12 national journals indexed by SINTA, DOAJ or EBSCO. The eligibility criteria are that the research must be a quantitative method, the experimental method, the journal is published in 2022-2025, the research must be relevant, the participants come from elementary, junior high, high school and college students. Data analysis is quantitative analysis with the help of JASP applications. The results of this study can be concluded that there is a significant influence of the deep learning model in science learning with an effect size value of 0.915 in the high effect size category. These findings explain that the deep learning model is effectively applied at the elementary school to university education levels.